Future distribution of demersal species in a warming Mediterranean sub-basin - Panzeri, Diego; Reale, Marco; Cossarini, Gianpiero; Salon, Stefano; Carlucci, Roberto; Spedicato, Maria Teresa; Zupa, Walter; Vrgoč, Nedo; Libralato, Simone (Frontiers in Marine Science, 2024)
Predicting range shifts of marine species under different CO2 emission of CO2 scenarios is of paramount importance to understand biodiversity and spatial potential changes in a context of climate change and to ensure appropriate management, in particular in areas where resources are also critical to fisheries. Important tools which use environmental variables to infer range limits and species habitat suitability are the species distribution models or SDMs. In this work, we develop an ensemble species distribution model (e-SDM) to assess past, present and future distributions under Representative Concentration Pathway (RCP) 8.5 of nine demersal species and hotspot areas for their two life stages (adult and juvenile) in the Adriatic and Western Ionian Seas in four